KOLABORASI DAN INOVASI : MENERAPKAN SCIENCE, TECHNOLOGY, ENGINEERING, ARTS, AND MATHEMATICS (STEAM) UNTUK PEMBELAJARAN HOLISTIK DI PERGURUAN TINGGI - Zahlimar; Siminto; Jimmy Malintang; Irmawati; Unan Yusmaniar Oktiawati; Al Ikhlas (EDU RESEARCH, 2024)
The Science, Technology, Engineering, Arts, and Mathematics (STEAM) approach has become an innovative paradigm in education, offering multidisciplinary integration to address 21st century learning challenges. This article discusses the importance of applying STEAM to create holistic learning in higher education. By integrating science, technology, engineering, arts and mathematics, this approach aims to develop critical thinking skills, creativity, collaboration and innovation in students. Through the collaboration of various higher education institutions, this article explores STEAM implementation strategies in the curriculum, highlighting the role of each discipline to create integrative and relevant learning experiences. The study also includes an analysis of the challenges and opportunities in implementing STEAM concepts, including the adaptation of technology and the role of art in enhancing students' innovativeness. The results show that the STEAM approach can increase students' engagement in learning, strengthen their problem-solving skills, and prepare them for the dynamic world of work. Therefore, the application of STEAM is recommended as a sustainable educational model to support the transformation of education in higher education.